Visual Comfort Parameters for Classrooms and the Effect of Interior Surfaces - Aydin Yagmur, Sensin; Serefhanoglu Sozen, Mujgan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2016)
A special period of development is experienced in classrooms. Because visual perception is the most effective means of learning, visual comfort in classrooms has prime importance regarding the performance of educational activity without difficulty, fatigue, or loss of efficiency. Interior surface features affect visual comfort, as do lighting quantity and quality. In the present study, primary factors affecting visual comfort in classrooms are presented, and luminance values of inner surfaces are exemplified with a lighting design program. In addition, results of surveys regarding surface features of work tables in a classroom of the Yildiz Technical University Department of Architecture are presented.
Keywords: Classroom; visual comfort; luminance; Architecture